Theoretical Approaches аnd Program-Target Method in the Regional Study оf Youth Migration - N. A. Shchitova; V. S. Belozerov; Ju. F. Zolnikova; P. M. Polyan (Наука. Инновации. Технологии)
Introduction. In the article, based on the analysis of a theoretical review of literature sources and reliance on a program-targeted approach has been developed conceptual scheme and program for a comprehensive study of youth migration for two contrasting regions of the South in many respects European Russia - Stavropol Territory and the Republic of Dagestan.Materials and research methods. The source materials were publications of domestic and foreign authors on youth migration issues in recent years thirty years.Research results and their discussion. The analysis showed that most of the studies youth migration is based on the analysis of statistical data and using various, including qualitative, sociological methods. Publications of an empirical nature predominate and reflect the results specific studies at country or regional levels. Developed conceptual scheme for studying youth migration in the peripheral territories of the South of European Russia using the example Stavropol Territory and Dagestan includes problem statement and determination within its framework of a specific goal, formulation of problematic questions and hypotheses, spatiotemporal framework of the study; his information and tool base. Feature Comparative Research Program spatial differentiation of youth migration in Stavropol region and the Republic of Dagestan includes five stages: preparatory - collection and systematization of statistical and documentary information about youth migration in the Stavropol Territory and Dagestan; sociological research; analytical – identification of spatial features youth migration in Dagestan and Stavropol Territory; practical – development of applied aspects, implementation of research results in practical activities of the authorities of the Stavropol Territory and Republic of Dagestan. Each stage includes intermediate goals, methods their achievements, a list of planned results.Conclusions. The current state of research in the field of youth migration, approaches to determining basic concepts The presented concept of youth migration research, reflects the main author’s approaches to its study and acts theoretical basis for the implementation of a program-targeted approach when developing a program for specific research on migration processes in youth environment in the South of European Russia.